2023
DOI: 10.3390/pathogens12020208
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological Survey in European Brown Hare (Lepus europaeus Pallas, 1778) Breeding Facilities in Southern Italy

Abstract: Parasites are considered important regulating factors of hosts’ population dynamics, not only in free-ranging wildlife, but also in captive bred animals. To date, only few studies have been carried out to assess the parasitic communities of the European brown hare in Southern Italy, and only one focused on animals in captivity. The aim of the present survey was to assess the composition of the endoparasite community in game hares bred for restocking purposes. For this purpose, 215 fecal pools collected in eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition to the oriental eye worm, European brown hares can harbour a wide diversity of endoparasites, including protozoans, trematodes, cestodes and nematodes. The survey performed by Brustenga et al [10] in Italy on 215 faecal samples from European brown hares bred for restocking purposes showed that the most prevalent parasites belonged to the genus Eimeria (91.2%), followed by the nematodes Trichostrongylus retortaeformis (21.4%), Passalurus ambiguous (9.3%), and Strongyloides papillousus (6.5%), the cestode Cittotenia spp. (5.6%), and the trematode Dicrocoelium dendriticum (1.4%).…”
Section: Wildlifementioning
confidence: 99%
“…In addition to the oriental eye worm, European brown hares can harbour a wide diversity of endoparasites, including protozoans, trematodes, cestodes and nematodes. The survey performed by Brustenga et al [10] in Italy on 215 faecal samples from European brown hares bred for restocking purposes showed that the most prevalent parasites belonged to the genus Eimeria (91.2%), followed by the nematodes Trichostrongylus retortaeformis (21.4%), Passalurus ambiguous (9.3%), and Strongyloides papillousus (6.5%), the cestode Cittotenia spp. (5.6%), and the trematode Dicrocoelium dendriticum (1.4%).…”
Section: Wildlifementioning
confidence: 99%